Urban redevelopment and decarbonization challenges. An overview from the real estate market perspective - Liddo, Felicia Di; Amoruso, Paola; Tajani, Francesco; Morano, Pierluigi; Stara, Federico (Energy and buildings, 2025)
•The review concerns the topic of urban and energy regeneration.•Energy retrofit, urban redevelopment and real estate market dynamics are pointed out.•Scientific and academic literature is investigated. In the light of the recent intentions of the European Union, the issue of decarbonisation has become critically important in the building sector. The coherence between the attention of policy makers towards the issues of decarbonisation and urban regeneration and the higher academic interest can be linked to the current needs of sustainability and the climate objectives. The present review aims to provide a general framework of the state of knowledge on the broad topic, focusing on the investigation of the interrelationships existing between energy retrofit interventions, urban redevelopment and the consequent dynamics of the real estate market. The study has been developed as a systematic analysis of the existing literature on the topic in order to point out the main explored aspects, the geographical contexts, the investigated market segments and the most used methodological approaches. Specifically, 167 papers have been analyzed, whose 44 % investigates the relationship between energy retrofit and real estate market, 39 % explores the link between the urban regeneration and property sector and 17 % points out the effects of dynamics of the real estate market on urban transformation interventions. To summarize some of the most significant data regarding the estimated sample, approximately 75 % of the articles has been published after 2016, around 50 % focuses on the European context, more than half of the papers addresses the residential sector and the majority of the contributions (approximately 70 %) consists of scientific Journal articles. In particular, approximately 50 % explicitly indicates the increase in real estate value resulting from the implementation of an energy retrofit/urban redevelopment intervention. Descending from the above, the review provides a valuable reference to address the subjects involved in building and urban renewal operations towards profitable and effective choices.